EFFECTIVENESS OF RESISTANCE TRAINING ON THE STRENGTH OF SCAPULO-HUMERAL MUSCLES AND ABDOMINALS IN MALE VOLLEY BALL PLAYERS (International Journal of Physiotherapy, 2014)
Background: Volleyball is a sportive modality that requires strength in the upper and lower extremities along with the trunk musculature. The improvement of muscular strength is very important along with agility and flexibility for a volleyball player. Aim of the study to find the effectiveness of resistance training on the strength of scapulo-humeral muscles and abdominals in male volley ball players. Objectives of this study is find out the effect of resistance training on the strength of the scapulo-humeral muscles by measuring peak torque by using an isokinetic dynamometer and to find out the effect of resistance training on strength of abdominals through 1RM test.Methods: A group of 30 male volleyball players who have fulfilled the inclusion criteria were assigned into two groups control and experimental groups each consisting of 15 subjects. The subjects of the experimental group underwent resistance training under my supervision and the subjects of the control group done the same protocol unsupervised for 6 weeks.Results: There was significant improvement in the strength of scapula-humeral muscles and abdominals in the experimental group when compared to the control group when the pre and post intervention values were measured (p=0.05).Conclusion: Resistance training under supervision of the therapist resulted in significant improvement in strength of the scapulo-humeral muscles and abdominals in the male volleyball players.